Transport Properties of Co in Cu(100) from Density Functional Theory Calculations - García Fernández, Carlos (2017)
The electronic transport properties of a point-contact system formed by a single Co atom adsorbed on Cu (100) and contacted by a copper tip is evaluated in the presence of intra-atomic Coulomb interactions and spin-orbit coupling. The calculations are performed using equilibrium Green's functions evaluated within density functional theory completed with a Hubbard U term and spin-orbit interaction, as implemented in the Gollum package. We show that the contribution to the transmission between electrodes of spin-flip components is negative and scaling as λ2/Δ2 where λ is the SOC and Δ the Co atom-electrode coupling. Hence, due to this unfavorable ratio, SOC effects in transport in this system are small. However, we show that the spin-flip transmission component can increase by 2 orders of magnitude depending on the value of the Hubbard U term. These effects are particularly important in the contact regime because of the prevalence of d-electron transport, while in the tunneling regime, transport is controlled by the sp-electron transmission, and results are less dependent on the values of U and SOC. Using our electronic structure and the elastic transmission calculations, we discuss the effect of U and SOC on the well-known Kondo effect of this system.